Longitudinal changes in musculoskeletal findings of elementary and junior high school students: a 1-year prospective study - Taishu Kasai; Hiroshi Kamada; Yohei Tomaru; Yuta Tsukagoshi; Tomofumi Nishino; Masashi Yamazaki; Shumpei Miyakawa; Hitoshi Shiraki (Japanese Society of Physical Fitness and Sports Medicine, 2020)
The purpose of this study was to investigate the characteristics of musculoskeletal findings in elementary and junior high school children using 1-year prospective longitudinal data from a long-term survey. Data from 1209 (97.6%) of 1239 children were analyzed. The main results were as follows: "Limitation of standing forward flexion" was particularly frequent in the 4th grade in all children and in the 5th grade in boys and girls going on to the next grade. "Flat foot" was particularly frequent in boys in the 1st, 6th, and 8th grades going on to the next grade. In girls, the frequency of "flat foot" was particularly high in the 1st, 4th, and 8th grades going on to the next grade. Findings of scoliosis appeared more often in girls than in boys. Minor findings such as "asymmetrical height of the shoulder and scapula", first appearing in the 4th and 5th grades, may be linked to the increase in "Rib hump" in the stage entering junior high school; it is important to pay attention to such changes in the scoliosis findings. This 1-year prospective longitudinal analysis demonstrated that the frequency of some musculoskeletal findings was high. We suggest that an extended longitudinal study will contribute to a better understanding of the relationship between the appearance of musculoskeletal findings and growth and development in school children. Accordingly, further analysis of the various stages of growth and development are needed.